Left Main Coronary Revascularization - Cortese, Bernardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book comprehensively reviews LM revascularization, one of the most technically challenging and prognostically relevant topics for cardiologists. LM carries blood to 70-80% of the normal heart, and diseases affecting this coronary segment are a common cardiac condition. Beginning in the sixties, management was exclusively within the domain of cardiac surgeons, and recent dramatic changes in percutaneous techniques have led to huge improvements but have also brought significant surgical challenges. In the book, top cardiac surgeons describe current and future operative techniques, while leading interventional cardiologists discuss new bifurcation techniques. This book also investigates the recently released European Society of Cardiology Guidelines in detail. Featuring the latest scientific studies with long-term follow up, and detailed descriptions of the techniques used, this book provides comprehensive guidance for any clinician, and is a valuable resource for cardiologists, interventional cardiologists, cardiac surgeons and internists.
1 Historical background of left main stem revascularization -- 2 Anatomical and pathophysiological considerations on the left main coronary artery -- 3 CABG vs. PCI for left main revascularization -- 4 CABG should be the first option for left main disease- a surgical perspective -- 5 Now, PCI should be the first option for left main disease- an interventional cardiologist's perspective -- 6 Which device for left main PCI? A description of available devices -- 7 Which interventional technique for left main PCI -- 8 Which surgical technique for left main coronary artery bypass? -- 9 Preoperative and postoperative IVUS assessment of the left main -- 10 Preoperative functional assessment of the left main and postoperative side branch evaluation -- 11 Is there a role for OCT for left main assessment before and after PCI? -- 12 The role of intravascular imaging for intraprocedural and post-procedural evaluation of the left main undergone PCI -- 13 Follow up of left main patients treated with PCI or CABG.
Keywords: Internal medicine; Surgery; Radiology; Emergency medicine; Medical policy; Internal Medicine; Surgery; Surgery; Radiology; Emergency Medicine; Health Policy; Myocardial Revascularization -- methods; Coronary Artery Disease -- surgery